The construct and longitudinal validity of the basketball exercise simulation test - Scanlan, A.; Dascombe, B. J.; Reaburn, P. R. J. (The Journal of Strength and Conditioning Research, 2012)
The purpose of this study was to assess the validity of the recently developed Basketball Exercise Simulation Test (BEST). Ten semiprofessional (age, 22.7 ± 6.1 years; height, 189.6 ± 9.5 cm; weight, 86.5 ± 18.7 kg; % body fat, 14.7 ± 3.5%) and 10 recreational (age, 26.6 ± 4.0 years; height, 185.9 ± 7.9 cm; weight, 92.6 ± 8.4 kg; % body fat, 23.8 ± 6.3%) male basketball players volunteered for the study. The participants completed a Yo-Yo Intermittent Recovery Test (Yo-Yo IRT) and BEST trial midway through the playing season. Eight participants (semiprofessional, n = 4; recreational, n = 4) completed an additional Yo-Yo IRT and BEST trial at the end of the playing season. Performance measures from the BEST included sprint decrement (%), mean sprint and circuit time (seconds), and total distance covered (m). Construct validity was calculated using Student's unpaired t-tests to identify the differences in Yo-Yo IRT and BEST performances between playing levels. Longitudinal validity was determined based on the relationship between changes (%) in Yo-Yo IRT1 and BEST performances across the season. Semiprofessional players performed significantly (p < 0.01) better in the Yo-Yo IRT (1,283 ± 62 vs. 636 ± 297 m) and BEST (mean sprint time: 1.45 ± 0.01 vs. 1.65 ± 0.03 seconds; mean circuit time: 18.98 ± 1.79 vs. 22.72 ± 2.01 seconds; sprint decrement: 8.54 ± 0.15 vs. 15.38 ± 0.27%) compared with recreational players. For the group as a whole, a strong relationship was evident between the changes in BEST sprint decrement and changes in Yo-Yo IRT performance (R = -0.815, p = 0.014) across the season. In conclusion, the BEST displayed both discriminative and longitudinal validities and provides a novel match-specific fitness test for basketball players.